Interventions to improve hospital patient satisfaction with healthcare providers and systems: a systematic review. Issue 7 (3rd August 2016) - Davidson, Karina W; Shaffer, Jonathan; Ye, Siqin; Falzon, Louise; Emeruwa, Iheanacho O; Sundquist, Kevin; Inneh, Ifeoma A; Mascitelli, Susan L; Manzano, Wilhelmina M; Vawdrey, David K; Ting, Henry H
Abstract : Background: Many hospital systems seek to improve patient satisfaction as assessed by the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) surveys. A systematic review of the current experimental evidence could inform these efforts and does not yet exist. Methods: We conducted a systematic review of the literature by searching electronic databases, including MEDLINE and EMBASE, the six databases of the Cochrane Library and grey literature databases. We included studies involving hospital patients with interventions targeting at least 1 of the 11 HCAHPS domains, and that met our quality filter score on the 27-item Downs and Black coding scale. We calculated post hoc power when appropriate. Results: A total of 59 studies met inclusion criteria, out of these 44 did not meet the quality filter of 50% (average quality rating 27.8%±10.9%). Of the 15 studies that met the quality filter (average quality rating 67.3%±10.7%), 8 targeted the Communication with Doctors HCAHPS domain, 6 targeted Overall Hospital Rating, 5 targeted Communication with Nurses, 5 targeted Pain Management, 5 targeted Communication about Medicines, 5 targeted Recommend the Hospital, 3 targeted Quietness of the Hospital Environment, 3 targeted Cleanliness of the Hospital Environment and 3 targeted Discharge Information. Significant HCAHPS improvements were reported by eight interventions, but their generalisability may be limited by narrowly focused patient populations, heterogeneity of approach and other methodological concerns. Conclusions: Although there are a few studies that show some improvement in HCAHPS score through various interventions, we conclude that more rigorous research is needed to identify effective and generalisable interventions to improve patient satisfaction.